Flowering Stimulation of Super Red Dragon Fruit (Hylocereus costaricensis (F. A. C. Weber) Britton & Rose) by Yellow Light and Boron Application - Indah Rohandani Putri MR; Trimurti Hesti Wardini; Taufik Taufikurahman (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Dragon fruit plants are long-day plants that require a long photoperiod to induce flowering, making light management an important factor in their productivity. In recent years, their declining yields in Indonesia have been linked to suboptimal flowering induction and fruit cracking, partly related to nutritional imbalances, particularly boron deficiency. This study aims to improve dragon fruit flowering by providing yellow light and adding boron. The study was conducted at the SITH Haurngombong Educational Orchard in Sumedang, using a randomized block design with three factors: light, boron, and plant age. The parameters observed included the number of flowers, the number of fruits, fruit weight, and cracked fruits. The results showed that the combination of light and boron significantly increased dragon fruit production, with the highest number of flowers (14.33±0.52) and number of fruits (14.33±0.52) found on 7-year-old plants; the heaviest fruit was from 3-year-old plants (483.71±13.83 g); and the lowest percentage of cracked fruit was observed in 7-year-old plants (3%). The light treatment enhances dragon fruit production, while boron supplementation reduces the number of cracked fruits. In general, the combination of yellow light and boron treatment was the most optimal in enhancing flowering in 3-year-old and 7-year-old plants compared to the control. As plants age, the quantity and quality of the fruit they produce increase. The findings of this study are expected to provide valuable insights for cultivating dragon fruit and offer practical guidance for optimizing flowering induction and improving fruit quality in commercial production systems.